2014
DOI: 10.1021/ac4037894
|View full text |Cite
|
Sign up to set email alerts
|

RNA Aptamer against Autoantibodies Associated with Multiple Sclerosis and Bioluminescent Detection Probe on Its Basis

Abstract: Nowadays, there are no specific laboratory tests for establishing the diagnosis of multiple sclerosis (MS). The presence of proteolytic autoantibodies against myelin basic protein is now considered as a characteristic feature of MS. New 2'-F-containing RNA aptamer of high affinity and specificity to these antibodies was selected. Covalent conjugate of this aptamer and Ca(2+)-regulated photoprotein obelin was obtained for the first time and applied as a label in bioluminescent microplate assay to detect target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…It is believed that MBP and anti-MBP Abs cannot interact with DNA or RNA. However, it was recently shown that anti-MBP IgGs can efficiently interact with nucleic acids [125]. Using quenching of MBP tryptophan fluorescence emission, we have shown that MBP bind oli- In the latter case, it is impossible to exclude possibility of a formation of the chimeric MLChs possessing affinity for MBP and for DNA and also hydrolyzing these absolutely different substrates.…”
Section: Resultsmentioning
confidence: 86%
“…It is believed that MBP and anti-MBP Abs cannot interact with DNA or RNA. However, it was recently shown that anti-MBP IgGs can efficiently interact with nucleic acids [125]. Using quenching of MBP tryptophan fluorescence emission, we have shown that MBP bind oli- In the latter case, it is impossible to exclude possibility of a formation of the chimeric MLChs possessing affinity for MBP and for DNA and also hydrolyzing these absolutely different substrates.…”
Section: Resultsmentioning
confidence: 86%
“…Current methods to diagnosis MS require multiple tests and are time consuming. Vorobjeva et al, recently developed an RNA aptamer-based biosensor for the detection of proteolytic autoantibodies against myelin basic protein, the presence of which is a characteristic feature of the disease [59]. A bioluminescent probe was prepared by conjugation of calcium-activated obelin to the RNA aptamer.…”
Section: Targets Relating To Demyelinating Disease and Spinal Cord Inmentioning
confidence: 99%
“…It is believed that MBP and anti-MBP Abs cannot interact with DNA or RNA. It was recently shown that anti-MBP Abs efficiently interact with nucleic acids [55]. It should be noted, that MBP is a very hydrophobic protein.…”
Section: Discussionmentioning
confidence: 99%